Muhammadiyah identity and Muslim public good: Muslim practices in Java - Qodir, Zuly; Jubba, Hasse; Mutiarin, Dyah; Hidayati, Mega (Penerbit Universiti Kebangsaan Malaysia, 2021)
The study in the current article intends to explore the conception of the presence of the Islamic religious movement known as Muhammadiyah, which still remains to this day in relation to the life of the Muslim community, including its socio-religious, cultural, economic, and political aspects. Accordingly, a proper understanding of Muhammadiyah is not only achieved through a religious approach, but also by examining social-historical conditions, which is by demonstrating the extent that its presence in conducting religious activities correlates with the true concept of Islam (Muslim Public Good). The current study aims to observe the models and strategies utilized by Muhammadiyah’s champions in repositioning and reflecting on religious movements, which have been framed at both conceptual and practical level. Subsequently, the framing strategies were used as a social capital to carry out their religious activities. For issues that are practical in nature, the study in this article is a description and elaboration about the aspirations, perceptions, intentions, ideas, goals, and thoughts pertaining to a social system inspired by the spirit of religiosity in Indonesia, in general, and Islam in Java, in particular, within the Muhammadiyah tradition as a Muslim public good (the true Islam).